Copolymerization of Phthalic Anhydride with Epoxides Catalyzed by Amine-Bis(Phenolate) Chromium(III) Complexes - Bukowski, Wiktor (Polymers (Basel), 2021)
The effect of ligand structure on the catalytic activity of amine-bis(phenolate) chromium(III) complexes in the ring-opening copolymerization of phthalic anhydride and a series epoxides was studied. Eight complexes differing in the donor-pendant group (R(1)) and substituents (R(2)) in phenolate units were examined as catalysts of the model reaction between phthalic anhydride and cyclohexane oxide in toluene. They were used individually or as a part of the binary catalytic systems with nucleophilic co-catalysts. The co-catalyst was selected from the following organic bases: PPh(3), DMAP, 1-butylimidazole, or DBU. The binary catalytic systems turned out to be more active than the complexes used individually, and DMAP proved to be the best choice as a co-catalyst. When the molar ratio of [PA]:[epoxide]:[Cr]:[DMAP] = 250:250:1:1 was applied, the most active complex (R(1)-X = CH(2)NMe(2), R(2) = F) allowed to copolymerize phthalic anhydride with differently substituted epoxides (cyclohexene oxide, 4-vinylcyclohexene oxide, styrene oxide, phenyl glycidyl ether, propylene oxide, butylene oxide, and epichlorohydrin) within 240 min at 110 °C. The resulting polyesters were characterized by M(n) up to 20.6 kg mol(−1) and narrow dispersity, and they did not contain polyether units.